PENYUTRADARAAN DENGAN GAYA INTERAKTIF DALAM PRODUKSI KARYA FEATURE “PIJAR ISLAM EPISODE MASJID JOGOKARIYAN” - Gilang Nursalam; Hans Hermang Mintana; Wahyu Sudarmawan (AKADEMI KOMUNIKASI RADYA BINATAMA, 2023)
ABSTRACT Mosques are not only places used for ritual worship, but also as a means for carrying out social activities, education, and as a means of strengthening social interaction in society. The Jogokariyan Mosque, located in Mantrijeron District, Jogjakarta City, has successfully transformed into a mosque that is famous for its good and innovative management and programs, especially during the month of Ramadan where there is the Jogokariyan Ramadhan Village Festival. This content is suitable to be presented in an audio-visual work in feature format. This feature work entitled